A structural model to study the bail-out process in a bank and its macro-prudential policy implications - Ricardo Correia; Javier Población; Tomasz Piotr Dubiel-Teleszynski (European Central Bank (ECB), 2017)
In this paper, we construct a structural model to determine the costs of a bank rescue considering bail-outs and bail-ins. In our model, a government assumes the equity stake under unlimited liability upon abandonment of the original equity holders. The model determines an abandonment trigger such that if total income drops below this trigger, private shareholders abandon the bank. Given this trigger, the model also determines the bank rescue costs, the expected time to the bank rescue and the bank rescue probabilities. A static analysis of our model produces several empirically testable hypotheses. The model was explored in a sample of southern European countries considering alternative assumptions regarding parameter estimates and the behavior of operational costs. The model results regarding the rescue costs are reasonable, but the model also predicts bank rescues, estimates equity values, performs welfare analyses and estimates the impact of different macro- and micro-prudential policies. The empirical exercise we present, highlights the importance of the assumptions made regarding the behavior of the operational costs by showing dramatic differences in results in a sample of countries that otherwise appear to share important cultural and geographical proximities.
Keywords: G21; G28; H81; 330; structural model; abandonment trigger; bank bail-out; macro-prudential policies